Análise farmacoepidemiológica e farmacoeconômica do tratamento da espondilite anquilosante com os bloqueadores do fator de necrose tumoral (TNF) - Marina Amaral de Avila Machado (2015)
Introduction. Ankylosing spondylitis (AS) is a chronic disease that primarily affects the spine and is characterized by inflammation and pain. In the Brazilian Health System (SUS) the disease-modifying antirheumatic drugs (DMARD) and the tumor necrosis factor (TNF) blockers, including infliximab, etanercept and adalimumab, are available for the treatment of AS. The anti-TNF are recommended for patients with persistent disease activity despite therapy with nonsteroidal anti-inflammatories for three months. The anti-TNF agent golimumab is not incorporated into the SUS for AS therapy. Objectives. To assess the efficacy, effectiveness, safety, cost and cost-utility of the AS therapy with anti-TNF agents infliximab, etanercept, adalimumab, and golimumab. Methods. A systematic review and meta-analysis of randomized clinical trials were performed to evaluate efficacy and safety and a 12-month follow-up prospective cohort was carried out to evaluate effectiveness and safety of AS therapy with anti-TNF agents. The efficacy and effectiveness was assessed by measures of disease activity, functionality and quality of life. A 3.5-year follow-up retrospective cohort of AS patients was conducted with data obtained from administrative databases of the SUS in Minas Gerais. The persistence on therapy with anti-TNF agents and DMARDs and the drug monthly cost per individual were estimated. A 8-year follow-up retrospective cohort with SUS administrative databases in Brazil was conducted to assess the risk of hospitalization for infections associated with anti-TNF therapy and DMARD exposure in patients with AS and rheumatoid arthritis (RA), considering drug exposure a time-dependent variable. The cost-utility analysis from the SUS perspective comparing etanercept and golimumab was perfomerd with 5 and 25-year time horizon and 5% discount on costs and benefits. Only direct medical costs were included and sensitivity analyses were performed to ensure the robustness of results. For all analyses a 5% significance level was adopted. The meta-analysis was conducted on Review Manager® 5.1, the statistical analyses of observational studies were performed on SAS 9.4 and the TreeAge Pro 2014 was used to run the economic model. Results. The systematic review included eighteen studies and the meta-analyses showed that patients treated with anti-TNF agents were more likely to achieve ASAS 20 response at 12/14 weeks (relative risk RR 2.21; confidence interval CI 95% 1.91; 2.56) and at 24 weeks (RR 2.68; CI 95% 2.06; 3.48) compared to control group. Meta-analyses of safety outcomes and withdraw showed non-statisticall results. The prospective study included 98 patients and 64.9% achieved good clinical response at 6 months of follow-up and 93 adverse reactions were reported. The retrospective cohort of Minas Gerais included 1,251 AS patients. At the first year of follow-up, 79.0% of the anti-TNF (+/-DMARD) group and 41.1% of DMARD-only group persisted on therapy. The monthly median cost was R$60 for DMARD therapy and R$3,956 for anti-TNF therapy. Among the anti-TNF agentes, etanercept had the lowest cost. The nationwide retrospective cohort included 86,398 patients with AS or RA and the rate of first hospitalization for infections was 6.08, 7.62, 4.83 and 7.57 per 1000 patient-years for non-user, DMARD, anti-TNF and anti-TNF+DMARD exposure, respectively. The adjusted hazard ratio (HR) (95% CI) was 1.27 (1.10; 1.47) to current DMARD exposure and 0.85 (0.67; 1.09) to current anti TNF exposure compared with non-use exposure. The adjusted HR of current anti-TNF+DMARD exposure compared to the non-use exposure was 1.36 (0.90; 2.05). The cost-utility model indicated that at 5 and 25 years golimumab is less costly and less effective compared to etanercept and the incremental cost-effectiveness ratio (ICER) was R$311,341.41 and R$157,185.80 per years of quality-adjusted life (QALY) in 5 and 25 years, respectively. Conclusions. The anti-TNF agents are effective in AS therapy and are associated with the occurrence of infections and other adverse reactions. However, the risk of serious infections associated to anti-TNF exposure did not differ from non-use. These drugs largely contribute to the high therapy cost of AS. The therapy with etanercept showed lower cost per patient compared to adalimumab and infliximab. Golimumab was considered a cost-effective alternative in the SUS perspective, however, this result shows considerable uncertainty and further studies should be conducted before the incorporation of this technology in the SUS. Keywords: ankylosing spondylitis, tumor necrosis factor (TNF) blocker, cohort study, cost-effectiveness study, health technology assessment